Frontiers of Blood Pressure and Heart Rate Analysis - Rienzo, M. Di (IOS Press, 2014)
An increasing number of studies indicate that the analysis of blood pressure and heart rate variability may be a valuable tool for the investigation of the mechanisms responsible for cardiovascular regulation in physiological and pathological conditions. The reader can find in the first part of this book an updated review of the techniques currently employed for the computer analysis of these signals with a particular attention to the most innovative approaches based on the non-linear analysis (including applications of the chaos theory, fractal analysis, I/f modelling) and the time-variant estimation of BP and HR characteristics. The biological interpretation of the results obtained by these computerized procedures and the applicability of these techniques in a clinical setting are fully addressed in the second part of the book.